Diseño y construcción de una bomba peristáltica. - Veintimilla Toro, Ronny Oliver (2015)
This project consist of the design and construction of a peristaltic pump and the implementation of it, its drive is produced by a geared motor of 0.5 hp. The peristaltic pump is a kind of positive displacement pump that comprises a power system 1/2 Hp (gear motor), a pumping system formed by a case shaped as half-moon a displacement mechanism (rotor, hose reels) and also by a structural system that serves as a base or support thereof. The pump is designed to operate at a speed of 26 rpm; the geared motor rotor induces the movement of the machine allowing that the coupled rollers therein, press the hose located in the half-moon achieving the fluid displacement. To design the different parts of the pump an analysis of strength of materials was made and workable materials were chosen to build it. The detail design was developed using the Auto CAD program; and then when machine worked the flow characteristics, volume and performance were analyzed.